Epitaxial and atomically thin graphene–metal hybrid catalyst films: the dual role of graphene as the support and the chemically-transparent protective cap. Issue 6 (20th April 2018) - Abdelhafiz, Ali; Vitale, Adam; Buntin, Parker; deGlee, Ben; Joiner, Corey; Robertson, Alex; Vogel, Eric M.; Warner, Jamie; Alamgir, Faisal M.
Abstract : Revolutionary catalyst protection by single layer graphene capping, tremendous catalyst lifetime longevity and activity enhancement towards oxygen reduction reaction. Abstract : In this study, we demonstrate dual roles for graphene, as both a platform for large-area, fully-wetted growth of two-dimensional Pt films that are one monolayer to several multilayers thick, while also serving as a 'chemically transparent' barrier to catalytic deactivation wherein graphene does not restrict the access of the reactants but does block Pt from dissolution or agglomeration. Using these architectures, we show that it is possible to simultaneously achieve enhanced catalytic activity and unprecedented stability, retaining full activity beyond 1000 cycles, for the canonical oxygen reduction reaction (ORR). Using high resolution TEM, AFM, X-ray photoemission/absorption spectroscopy (XPS/XAS), Raman, and electrochemical methods, we show that, due to intimate graphene–Pt epitaxial contact, Pt_ML/GR hybrid architectures are able to induce a compressive strain on the supported Pt adlayer and increase catalytic activity for ORR. With no appreciable Pt loss or agglomeration observed with the GR/Pt_ML catalysts after 1000 ORR cycles, our results open the door to using similar graphene-templated/graphene-capped hybrid catalysts as means to improve catalyst lifetime without a necessary compromise to their activity. More broadly, the epitaxial growth made possible by the room-temperature, wetted synthesis approach, should allow for efficient transfer of charge, strain, phonons and photons, impacting not just catalysis, but also electronic, thermoelectric and optical materials.